Aromatase Gene Expression in N-Ethyl-Nitrosamine-Induced Hepatocellular Carcinoma: Hepatoprotective Effects of Grape Seed Extract and Letrozole - Sadia Kazi; Sadia Tabassum; Bushra Sajid; Kishwar Lakhair; Shahnaz Bano; Mozna Talpur (Annals of Abbasi Shaheed Hospital and Karachi Medical & Dental College)
Objective: To determine the hepatoprotective properties of Letrozole alone and in combination with grape seed extract on hepatocellular carcinoma induced by N-Ethylnitrosamine in male albino Wistar rats. Methods: A quasi-experimental study was conducted at Sindh Agriculture University and Diagnostic Laboratory of Isra Hospital. Fifty albino Wistar rats, 200-250 g in weight, were allocated into five equal groups. Group A control group, Group B were induced with N- Ethylnitrosamine of 30mg/kg for 11 weeks, Group C was given N- Ethylnitrosamine of 30mg/kg and Grape Seed Extract of 100mg/kg for 11 weeks, Group D was given N- Ethylnitrosamine of 30mg/kg and Letrozole of 2mg/kg for 11 weeks and E were given N- Ethylnitrosamine of 30mg/kg, Grape Seed Extract 100mg/kg and Letrozole of 2mg/kg for 11 weeks. Blood samples for liver enzymes, albumin, and hepatic tissue samples for histopathology were collected at the end of the study. Data regarding liver enzymes and aromatase gene expression was analyzed using SPSS (version 22, pd”0.05, 95% confidence). Results: There was a statistically significant (p < 0.05) difference in the mean levels of albumin and liver enzymes i.e. AST, ALT, and GGT across experimental groups. A relative aromatase gene expression of 21.13 ± 3.59, 36.22 ± 3.15, 28.61 ± 2.71, 46.66 ± 2.61, and 35.24 ± 3.48 was observed in Groups A, B, C, D, and E, respectively. The difference was statistically significant (p<0.05). There was a marked deterioration of the hepatic architecture in Group B. Similar changes with varying degrees were observed in experimental groups and group C showed the best results. Conclusion: Grape Seed Extract and Letrozole significantly affected liver enzyme levels, hepatic architecture, and relative gene expression of the aromatase gene. Additionally, individual therapy with grape seed extract exerts better effects against hepatocellular carcinoma induced by NEthylnitrosamine.